1998
DOI: 10.1111/j.1467-8624.1998.tb06198.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's and Adolescents' Understanding of Rights: Balancing Nurturance and Self‐Determination

Abstract: This study examined the development of young people's understanding of nurturance and self-determination rights. One hundred and sixty-nine participants from 5 age groups (8, 10, 12, 14, and 16 years of age) participated in a semistructured interview containing hypothetical vignettes, in which a story character wished to exercise a self-determination right or nurturance right that conflicted with the wishes or practices of those in authority. Participants were asked to decide if they would support the story ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
135
5
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 139 publications
(156 citation statements)
references
References 13 publications
13
135
5
1
Order By: Relevance
“…As in previous research on children's and adolescents' attitudes toward children's rights (e.g., Cherney & Perry, 1996;Cherney & Shing, 2008;Ruck et al, 1998;Ruck et al, 2002), in the current study participants were more willing to endorse asylum-seeking adolescents' and emerging adults' nurturance than self-determination rights. Extending past research, the findings revealed that participants showed similar support for nonreligious nurturance rights and religious self-determination rights followed by somewhat less support for asylum-seeker children's religious nurturance rights.…”
Section: Domain Considerationssupporting
confidence: 50%
See 4 more Smart Citations
“…As in previous research on children's and adolescents' attitudes toward children's rights (e.g., Cherney & Perry, 1996;Cherney & Shing, 2008;Ruck et al, 1998;Ruck et al, 2002), in the current study participants were more willing to endorse asylum-seeking adolescents' and emerging adults' nurturance than self-determination rights. Extending past research, the findings revealed that participants showed similar support for nonreligious nurturance rights and religious self-determination rights followed by somewhat less support for asylum-seeker children's religious nurturance rights.…”
Section: Domain Considerationssupporting
confidence: 50%
“…In contrast to past research on young people's conceptions of rights (e.g., Helwig, 1995Helwig, , 1997Ruck et al, 1998;Ruck et al, 2002), fewer age-related differences emerged in terms of reasoning than in endorsements. In the current investigation, agerelated differences were only found with regard to the justifications pertaining to ''outcomes'' for religious nurturance and self-determination vignettes.…”
Section: Age-related Findingscontrasting
confidence: 48%
See 3 more Smart Citations